Dampak Keamanan, Manfaat, Kepercayaan, Promosi, serta Kemudahan pada Keputusan Pemanfaatan Dompet Elektronik Shopeepay - Laila Ramadya Sari; Reni Anggraini; Mella Sri Kencanawati; Lana Sularto (METIK JURNAL, 2022)
In Indonesia, e-wallet payments are becoming a trend because of the many promotions and ease of use. The purpose of the study was to determine the impact of security, benefits, trust, promotion, and convenience on the decision to use the shopeepay e-wallet either partially or simultaneously. This study uses primary data. The stages of testing carried out are validity, reliability, normality, non-uniform variance, multicollinearity, multiple regression, coefficient of determination, F-test and t-test. The data is the result of the survey, and obtained 100 respondents with valid data. The research sample was taken through non-probability sampling with direct sampling technique and then tested using SPSS. The results of the study stated that only the convenience variable did not affect the decision to use the shopeepay electronic wallet, while the security, trust, benefits and promotion variables influenced the decision to use the shopeepay electronic wallet. However, simultaneously the variables of convenience, trust, security, benefits and promotions all influence the decision to use shopeepay e-wallet.